Determining adsorbate configuration on alumina surfaces with 13C nuclear magnetic resonance relaxation time analysis. Issue 32 (28th August 2015) - Vecino, P. A.; Huang, Z.; Mitchell, J.; McGregor, J.; Daly, H.; Hardacre, C.; Thomson, J. M.; Gladden, L. F.
<x xml:space="preserve">Abstract</x> Relative strengths of surface interaction for individual carbon atoms in acyclic and cyclic hydrocarbons adsorbed on alumina surfaces are determined using chemically resolved 13C nuclear magnetic resonance (NMR) T1 relaxation times.